Irreducible anteromedial radial head fracture-dislocation: value of pre-operative magnetic resonance imaging - Lim, Lee Kai (BJR Case Rep, 2020)
We describe a case of an anteromedial fracture-dislocation of the radial head in an adult patient, which was initially irreducible using closed means, and remained challenging to reduce despite open surgery. Further advanced CT/MRI revealed entrapment of the radial head due to the interposition of the brachialis tendon posteriorly, thereby preventing sustained reduction. While three other cases of irreducible anteromedial radial head dislocation due to the brachialis tendon have been reported in the English surgical literature, none of the imaging findings have been described in the radiological literature. Only one other case published in a surgical journal briefly demonstrated pre-operative MRI imaging. We would like to share the value of pre-operative MRI in this rare presentation, which would be helpful in diagnosing not only cases with interposition of the brachialis tendon, but potentially other types of soft tissue interposition which also limit closed reduction. To the best of the authors’ knowledge, this would be the first report on the imaging findings in a radiological journal. Awareness of this phenomenon would assist radiologists in the diagnosis and management of this rare condition.